Management Economics in a Large Retail Company - Siebert, W. Stanley; Zubanov, Nikolay (Management Science, 2010)
We use unique data from 245 stores of a UK retailer to study links among middle (store) manager skills, sales, and manager pay. We find that, of the six management practice areas surveyed, the most important is “commercial awareness,” where abler managers achieve up to 13.9% higher sales per worker. We find that many stores have poor managers on this indicator. However, the company is careful to incentivize managers, operating a scheme giving shares (approximately 20%) in both positive and negative deviations of actual sales from expected. Abler managers do not receive higher pay, implying that their skills are company specific.